2022
DOI: 10.1371/journal.pone.0277547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant density on the aboveground dry matter and radiation-use efficiency of field corn

Abstract: The amount of solar radiation intercepted by the plant canopy drives crop plant photosynthesis and the formation and development of plant organs. Radiation-use efficiency (RUE) is an index used to quantify the relationship between solar radiation and biomass, and crop yield can be increased by increasing RUE. The main goals of this study were to initially investigate the effects of plant densities on the aboveground dry matter of corn, and subsequently examine the effects of plant densities on RUE and leaf are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…In addition to the optimized position of the crop cycle within the growing season, the results of the present study have also shown the advantage of applying a high plant density (HiD) for maize, compared to the standard one (StD), to obtain a high methane yield, which had previously been reported for both maize grain [24] and biomass [55]. The enhanced plant density increased the lead area index [56], thus leading to a positive result on the cumulative amount of intercepted incident photosynthetically active radiation and, consequently, on maize biomass production [57]. Moreover, the increase in plant density did not change the BMP of whole-crop maize, thus confirming previous finding [16,55].…”
Section: Discussionsupporting
confidence: 75%
“…In addition to the optimized position of the crop cycle within the growing season, the results of the present study have also shown the advantage of applying a high plant density (HiD) for maize, compared to the standard one (StD), to obtain a high methane yield, which had previously been reported for both maize grain [24] and biomass [55]. The enhanced plant density increased the lead area index [56], thus leading to a positive result on the cumulative amount of intercepted incident photosynthetically active radiation and, consequently, on maize biomass production [57]. Moreover, the increase in plant density did not change the BMP of whole-crop maize, thus confirming previous finding [16,55].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, cultivars used in the early period of the experiments are no longer cultivated today. It is also difficult to thoroughly account for other factors that may affect crop growth, such as soil fertility, insects, disease, and plant density ( Altieri & Nicholls, 2003 ; Chen, Yamagishi & Kishino, 2014 ; Chen et al, 2019 ; Chen, 2019 ; Li, Dai & Chen, 2022a , 2022b ); as well as for human-induced effects, such as improving technology, modern management, and differences in practices of cultivators ( Chen, 2018 , 2019 ), especially for over nine decades of observations. Nowadays, climate change also includes the increasing frequency of extreme climatic events, which results in frequent agricultural meteorological disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Wheat yield under suitable water and nutrient conditions has been demonstrated to be closely associated with the amount of radiation intercepted during the growing season [1]. The primary abiotic variables influencing crop growth, development, and yield are temperature, moisture content, and nutrient availability.…”
Section: Introductionmentioning
confidence: 99%